A New Elastoplastic Time-History Analysis Method for Frame Structures - Qianqian Liang; Chen Zhao; Jun Hu (Advances in Civil Engineering)
This study aimed to analyze the formation and application of the time-domain elastoplastic response spectrum. The elastoplastic response spectrum in the time domain was computed according to the trilinear force-restoring model. The time-domain elastoplastic response spectrum corresponded to a specific yield strength coefficient, fracture stiffness, and yield stiffness. However, the force-restoring models corresponding to different structural systems and the states of the structural systems at different moments were not the same. Therefore, the dynamic characteristics of a particular periodic point corresponding to a particular structure were meaningful for the elastoplastic response spectrum. In addition, the curve in the time-domain dimension along the periodic point truly reflected the real-time response of the structure when the structure encountered a seismic load.